2012
DOI: 10.1111/j.1745-4549.2012.00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination Effect of Essential Oils of Some Herbs With Monolaurin on Growth and Survival ofListeria Monocytogenesin Culture Media and Cheese

Abstract: The antibacterial activity of tarragon, pennyroyal and spearmint EOs against Listeria monocytogenes in culture medium and fresh white cheese was evaluated alone, and in combination with monolaurin. Spearmint essential oil (EO) was the most effective, with minimum inhibitory concentration of 0.2% (v/v). The combination of monolaurin with EOs had an additive effect and fractional inhibitory concentration index of monolaurin–tarragon EO combination was the lowest (0.66). All the EOs, when added alone in the chees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The combination of monolaurin with each of these essences increased the anti-listeria effect, and MIC was found to be 0.66% in tarragon plus monolaurin. These results showed that using low concentrations of these substances in combination can have positive antimicrobial effects on foods (28), which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The combination of monolaurin with each of these essences increased the anti-listeria effect, and MIC was found to be 0.66% in tarragon plus monolaurin. These results showed that using low concentrations of these substances in combination can have positive antimicrobial effects on foods (28), which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Seven panelists were selected from the Department of Food Hygiene and Quality Control, University of Tehran, on the basis of their experience in the sensory analysis. The sensory parameters (appearance, taste, texture, and overall acceptability) were assessed using a 5‐point hedonic scale as like 5 indicated like extremely, 4 for like moderately, 3 for neither like nor dislike, 2 for dislike moderately, and 1 indicated dislike extremely (Hamedi, Razavi‐Rohani, & Gandomi, ). Sensory examination was done at day 1 of storage.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, very little is known about the impact of adding EOs directly to milk before cheesemaking. Hamedi et al [28] showed that the efficacy of EOs against Salmonella spp. in cheese diminished significantly when the results were compared with those obtained using a laboratory medium.…”
Section: Introductionmentioning
confidence: 99%